Human Resource Assessment and Management - Aris, Affandy Agusman (PT FORMOSA CENDEKIA GLOBAL, 2024)
Carrying out performance assessments on employees and executives is very important because it can have an impact on improving the performance concerned. This increase in performance will automatically have an impact on improving organizational performance. In this case, the role of Human Resource Management is very strategic in creating value that is difficult for competitors to imitate, namely, the value of human resources which is realized in an intangible activity, this value is a response from superiors, subordinates, and the surrounding environment which is equivalent to that in shoulder. Through 360-degree assessment, you can create an effective feedback process on employee and manager performance. By assessing performance, goals focused on improving quality can be better observed. Therefore, such an assessment can support the achievement of competitive advantage.